Challenging the state devolution and the battle for partisan credibility : a comparison of Belgium, Italy, Spain, and the United Kingdom - Alonso, Sonia (Oxford : Oxford University Press, 2012)
Why do national governments implement devolution given the high risk that it will encourage peripheral parties to demand ever more devolved powers? The aim of 'Challenging the State' is to answer this question through a comparative analysis of devolution in four European countries: Belgium, Italy, Spain and the United Kingdom.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Decentralization in government; Decentralization in government -- European Union countries; State, The